Experimental research on fracture behavior of concrete after high temperature - Peng Qiu (Fracture and Structural Integrity)
High-strength concrete has been widely used in various complex buildings. The fracture and mechanical properties of high-strength concrete after fire have great research value. Based on the double K fracture model, the fracture properties of C70 strength grade concrete after being processed by high temperature of 25 C ~ 800 C were studied by three-point bending beam test. The change rules of fracture toughness KIC and fracture energy under different temperatures after being processed by high temperature were analyzed. The results showed that the initial crack toughness and instability toughness of C70 concrete decreased with the increase of temperature; the fracture energy first decreased rapidly and then decreased slowly with the development of temperature